(untitled) (Aintelia Science Notes, 2022)
The use of induction motors in industrial systems has been increasing rapidly in recent years. The main reasons for this it has low cost, does not require much maintenance, and has a robust structure. The scalar control method, which has a low system cost due to the need for a single sensor (speed sensor), is preferred for speed control of induction motor in this study. The speed of induction motor is realized with PI control method using TI Delfino F28335 processor and 3-phase inverter over Simulink external mode. Thanks to the designed control interface, it is possible to turn the system on and off, change the reference speed value, and observe the actual speed value numerically and graphically. In addition, the controller coefficients Kp and Ki values can be changed without reprogramming the processor.